PERBEDAAN BUDAYA: TANTANGAN MEMBANGUN KEPERCAYAAN ANTARA GURU BK DAN SISWA - Aldilla Risyanindya; Rafli Achmad Slamet, Septia Nur Pitri Utami, Salma Humairah Shalihah, Tiara Firgiyanti, Nadia Aulia (CV. Adiba Aisha Amira, 2026)
Multicultural is a word that is often used to describe cultural diversity. The interactions between guidance and counseling teachers and students are characterized by multicultural phenomena caused by various factors such as different cultural backgrounds, social and cultural changes, and globalization. This can lead to challenges such as miscommunication, stereotyping, and discomfort, but it also brings benefits such as opportunities for learning, mutual respect, and the development of multicultural counseling skills. Guidance and guidance teachers need to have adequate knowledge and skills to deal with this phenomenon and build trust with students from various cultures. The purpose of this research is to determine the trust challenges faced by guidance and counseling teachers in dealing with students who have different cultural backgrounds using a literature review study with qualitative methods through interviews and observations with guidance and counseling teachers at SMPN 2 Bandung. By increasing intercultural awareness and communication skills, guidance and counseling teachers can build stronger relationships with students and provide more effective student learning.